Bibliometrics analysis on the research status and trends of small bowel adenocarcinoma: 1923-2023 - Lu, Yao; Pan, Cheng C.; Hu, Xin; Sun, Jing (Frontiers in Oncology, 2024)
The aim of this research is to discuss the research status, hotspots, frontiers, and development trends in the field of small bowel adenocarcinoma based on bibliometrics and visual analysis by CiteSpace software.The relevant research articles on SBA from 1923 to 2023 were retrieved from the Web of Science Core Collection database. CiteSpace software was used to form a visual knowledge map and conduct analysis for the countries/regions, journals, authors, keywords, clusters, research hotspots and frontiers of the included articles.Results: There were 921 articles included, and the number of articles published during 1923-2023 is increasing. The country with the highest number of articles published was the United States (443, 38.76%), followed by Japan (84, 9.12%) and France (72, 7.82%). The author with the highest number of publications is Ansell, Overman MJ (33, 3.58%), and the author with the highest co-citation frequency is Overman MJ (218). Journal of Clinical Oncology is the journal with the highest publication frequency. The top five cluster groups were "chemotherapy", "inflammatory bowel disease", "celiac disease", "tumor" and "small intestine".The related disease, chemotherapy drugs, and treatment regimens of SBA form the main research fields, and prognosis and diagnosis are the research hotspots and trends.The global research field in SBA has expanded in the past 100 years.The prognosis and new diagnosis of SBA are hotspots in this field and require further study in the future.